2020
DOI: 10.1007/s42976-020-00115-z
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of some flag leaf and yield characteristics by half-diallel analysis in rice crops (Oryza Sativa L.)

Abstract: This study was conducted during 2018 and 2019 at the Rice Research and Training Centre farm, Sakha, Kafr el Sheikh, Egypt. Six genotypes of rice, Sakha 101, Giza 178, Irat 170, Wab-56-104, IR65500-127 and IR69853 were half-diallel crossed to estimate the combining ability effect as well as sink and yield potential in rice. Sink capacity (number of spikelets/panicle and 1000-grain weight), source leaf (flag leaf length, flag leaf width and flag leaf area), source-sink association (number of spikelets/panicle to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
5
9
0
Order By: Relevance
“…The ratio of GCA/SCA variances explained the majority of gene action responsible for the inheritance of particular traits. The number of spikelets per panicle and number of filled grains per panicle had high additive gene action and a GCA/SCA variance of more than one, which is similar to the previous reports [ 12 , 55 , 56 ]. For traits showing high additive gene action, the selection method of breeding has been suggested to develop pure lines with desirable characters, i.e., pure line selection and pedigree selection [ 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The ratio of GCA/SCA variances explained the majority of gene action responsible for the inheritance of particular traits. The number of spikelets per panicle and number of filled grains per panicle had high additive gene action and a GCA/SCA variance of more than one, which is similar to the previous reports [ 12 , 55 , 56 ]. For traits showing high additive gene action, the selection method of breeding has been suggested to develop pure lines with desirable characters, i.e., pure line selection and pedigree selection [ 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 90%
“…Mahalanobis’ D 2 and principal component analysis (PCA) are the powerful pre-breeding tools used to select the diverse germplasm for hybridization and to estimate each germplasm’s potentialities [ 9 ]. The combined use of these two techniques was attempted recently in rice accessions to assess the phenotypic diversity of various traits by Dhakal, Pokhrel, Sharma, and Poudel [ 8 ]; Tiwari et al [ 10 ]; and Lakshmi et al [ 11 ] For genetic analysis in breeding, different mating designs are being followed, viz., Line × Tester (L × T), biparental cross, polycross, North Carolina design (I, II and III), and diallel (I, II, III, and IV) [ 12 , 13 , 14 , 15 ]. Each design has its own advantages, but Griffing’s full diallel mating design uses a general linear model, which is a widely used technique to identify the genetic and maternal effect of specific traits and for choosing parents and hybrids with general and specific combining ability, respectively, in the desired direction, which can be deployed in plant breeding [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of variance revealed that mean squares due to parents v/s crosses were highly significant or significant for all the characters except flag leaf area in F 1 's. Similar result has also been supported by earlier researchers (Rahimi et al, 2010;Sanghera et al, 2012;Bassuony et al, 2021 andMazal et al, 2021).…”
Section: Analysis Of Variancesupporting
confidence: 85%
“…They disclosed that the additive gene effects contribute considerably to the inheritance of grain yield and several related traits in rice. On the contrary, other reports have found that non-additive gene action has a major role in the inheritance of agronomic traits in rice [ 17 , 19 , 75 ]. The significant GCA × I and SCA × I interactions for grain yield and most of the other studied traits indicate the differential performance of the parental genotypes and hybrids under distinct conditions.…”
Section: Discussionmentioning
confidence: 86%